The influence of the parasocial relationship on the learning motivation and learning growth with educational YouTube videos in self regulated learning - Beautemps, Jacob; Bresges, André (Frontiers in Education, 2022)
The parasocial relationship (PSR) or parasocial interaction (PSI) have been intensively researched in the field of marketing and television research. As a result, we know that viewers form strong relationships with presenters and this has a big impact for example in selling products. Whether this effect also has an impact on learning in educational videos has hardly been a focus of research. In this study, the correlation of PSI and learning growth, as well as learning motivation was investigated. It could be shown that there was no correlation between PSI and learning growth, but a slight correlation between PSI and learning motivation could be measured, especially with female participants. This offers a lot of potential for the creation of educational videos and at the same time could be an important finding for the training of teachers, because through previous research on PSI we already know factors with which the interaction and relationship can be improved.